2021
DOI: 10.1200/jco.21.02008
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Colorectal Adenocarcinoma in the IDEA Database: Treatment Adherence, Toxicities, and Outcomes With 3 and 6 Months of Adjuvant Fluoropyrimidine and Oxaliplatin

Abstract: PURPOSE Early-onset (EO) colorectal cancer (CRC, age < 50 years) incidence is increasing. Decisions on optimal adjuvant therapy should consider treatment adherence, adverse events, and expected outcomes in a population with life expectancy longer than later-onset (LO) CRC (age ≥ 50 years). MATERIALS AND METHODS Individual patient data from six trials in the International Duration Evaluation of Adjuvant Chemotherapy database were analyzed. Characteristics, treatment adherence, and adverse events in stage II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
49
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 13 publications
7
49
2
Order By: Relevance
“…Simultaneously, efforts must be put into understanding the biology of this heterogenous disease entity and determine how best to treat these patients to improve cancer outcomes. Large trial populations such as those reported by Fontana et al 1 would ideally collect greater details of patient characteristics and comorbidities to help this understanding. Given the increasing incidence since the IDEA collaboration studies, we also need to explore changes that may have occurred over time to understand the increasing incidence.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Simultaneously, efforts must be put into understanding the biology of this heterogenous disease entity and determine how best to treat these patients to improve cancer outcomes. Large trial populations such as those reported by Fontana et al 1 would ideally collect greater details of patient characteristics and comorbidities to help this understanding. Given the increasing incidence since the IDEA collaboration studies, we also need to explore changes that may have occurred over time to understand the increasing incidence.…”
Section: To the Editormentioning
confidence: 99%
“…Fontana et al 1 have recently reported in the Journal of Clinical Oncology on the IDEA database. Historically, more than 90% of colorectal cancer (CRC) diagnosis occurred in patients > 50 years (late-onset CRC [LO-CRC]).…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…We thank Smith et al 1 for their correspondence in relation to our article. 2 The increased incidence in early-onset colorectal cancer (EO-CRC) was noticed since the beginning of the 90s in the United States, possibly highlighted by the accelerated opposite trends in adults older than 50 years as an effect of screening programs. 3 Importantly, this phenomenon has been observed with different magnitudes in different countries; this suggests that this is unlikely due only to screening programs masking a possible global increase, but more likely to different early-life cancerogenic exposure.…”
mentioning
confidence: 99%
“…The studies included in the IDEA database recruited patients from 2007 to 2017, thus during a relevant and contemporary timeframe, although limited. 2 In Figure 1, we present, to our knowledge, for the first time the accrual curve including the percentage of patients with EO-CRC by year. In view of different recruitment rates in each trial at different time points, changes in incidence are challenging to appreciate.…”
mentioning
confidence: 99%